Impact of Three Different Mutations in Ehrlichia chaffeensis in Altering the Global Gene Expression Patterns - Kondethimmanahalli, Chandramouli; Ganta, Roman R. (My University, 2018)
The rickettsial pathogen Ehrlichia chaffeensis causes a tick-borne disease, human monocytic ehrlichiosis. Mutations within certain genomic locations of the pathogen aid in understanding the pathogenesis and in developing attenuated vaccines. Our previous studies demonstrated that mutations in different genomic sites in E. chaffeensis caused variable impacts on their growth and attenuation in vertebrate and tick hosts. Here, we assessed the effect of three mutations on transcriptional changes using RNA deep-sequencing technology. RNA sequencing aided in detecting 66–80% of the transcripts of wildtype and mutant E. chaffeensis. Mutation in an antiporter gene (ECH_0379) causing attenuated growth in vertebrate hosts resulted in the down regulation of many transcribed genes. Similarly, a mutation downstream to the ECH_0490 coding sequence resulted in minimal impact on the pathogen’s in vivo growth, but caused major changes in its transcriptome. This mutation caused enhanced expression of several host stress response genes. Even though the ECH_0660 gene mutation caused the pathogen’s rapid clearance in vertebrate hosts and aids in generating a protective response, there was minimal impact on the transcriptome. The transcriptomic data offer novel insights about the impact of mutations on global gene expression and how they may contribute to the pathogen’s resistance and/or clearance from the host.
Citation: Kondethimmanahalli, C., & Ganta, R. (2018). Impact of Three Different Mutations in Ehrlichia chaffeensis in Altering the Global Gene Expression Patterns. Scientific Reports, 8(1). https://doi.org/10.1038/s41598-018-24471-3
Keywords: Bacteriology; Pathogens